THE ROLE OF CATALYSTS IN GREEN CHEMISTRY: TOWARDS SUSTAINABLE CHEMICAL PROCESSES - Hamid Javaid (Bulletin of Engineering Science, Technology and Industry, 2023)
The transition to sustainable chemical processes is a critical challenge in the 21st century, driven by the need to minimize environmental impact and enhance resource efficiency. Catalysts play a pivotal role in green chemistry, offering pathways to more sustainable industrial processes by increasing reaction efficiency, reducing energy consumption, and minimizing waste. This paper explores the fundamental principles of catalysts in green chemistry, their applications in various chemical processes, and future directions for research and development. By examining case studies and recent advancements, this research highlights the potential and challenges of catalysts in achieving sustainable chemical processes. Through the integration of homogeneous, heterogeneous, biocatalysts, photocatalysts, and electrocatalysts, this study underscores the essential contributions of catalysis to the goals of green chemistry and sustainable industry practices.